2019
DOI: 10.1186/s13000-019-0840-2
|View full text |Cite
|
Sign up to set email alerts
|

The importance of EGFR mutation testing in squamous cell carcinoma or non-small cell carcinoma favor squamous cell carcinoma diagnosed from small lung biopsies

Abstract: Background Adenosquamous carcinoma (ADSC) of the lung, a rare but aggressive subtype of non-small cell lung cancer (NSCLC), is defined as a carcinoma containing components of adenocarcinoma (ADC) and squamous cell carcinoma (SqCC). Mutations of epidermal growth factor receptor (EGFR) are found at a frequency of 15 to 44% in Asian ADSC, and EGFR tyrosine kinase inhibitors (EGFR-TKIs) are a more effective treatment for EGFR-mutated ADSC compared to chemotherapy. However, ADSC in small lung biopsies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
0
10
1
5
Order By: Relevance
“…EGFR mutations in patients with non-small-cell lung cancer (NSCLC) determine clinicopathology, prognosis and treatment strategies [2] and occur in 10-20% of Caucasian patients and 40-60% of Southeastern Asian patients with lung carcinoma [2]. In general, deletions in exon 19 (ex19del) and the point mutation in exon 21 (Leu858Arg) account for 90% of EGFR mutations in this disease setting [3], with ex19del accounting for 45% of patients and exon 21 (Leu858Arg) accounting for 40% of patients [4]. However, the rates of these mutations can vary by region [2,5], with exon 21 (Leu858Arg) being more prevalent in Asian countries, particularly in Japan [6,7].…”
mentioning
confidence: 99%
“…EGFR mutations in patients with non-small-cell lung cancer (NSCLC) determine clinicopathology, prognosis and treatment strategies [2] and occur in 10-20% of Caucasian patients and 40-60% of Southeastern Asian patients with lung carcinoma [2]. In general, deletions in exon 19 (ex19del) and the point mutation in exon 21 (Leu858Arg) account for 90% of EGFR mutations in this disease setting [3], with ex19del accounting for 45% of patients and exon 21 (Leu858Arg) accounting for 40% of patients [4]. However, the rates of these mutations can vary by region [2,5], with exon 21 (Leu858Arg) being more prevalent in Asian countries, particularly in Japan [6,7].…”
mentioning
confidence: 99%
“…They concluded that EGFR mutation testing should be performed in Asian patients with SqCC diagnosed from small lung biopsies, especially in never-smokers and patients with diagnosis of NSCC favor SqCC, which have a high probability of being adenosquamous carcinoma. 17 Tests of multiple biopsies are helpful for accurate pathological and molecular diagnosis. In our case, the patient was a young, light smoker, and diagnosis came from small biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Đa số bệnh nhân trong nghiên cứu là nam giới (90,9%), gấp khoảng 10 lần với bệnh nhân nữ giới. Trong nghiên cứu của Amit Joshi và cs (2017), phần lớn đối tượng nghiên cứu là nam giới, gấp khoảng 3 lần so với nữ giới; còn nghiên cứu Hsiang-Ling Ho và cs (2019) thì số lượng nam giới và nữ giới tương đương nhau [8,9]. Với mẫu mô FFPE, các mẫu chủ yếu được lấy bằng phương pháp sinh thiết (96,4%) và tại vị trí u phổi nguyên phát (87,8%).…”
Section: Bàn Luậnunclassified
“…Với mẫu mô FFPE, các mẫu chủ yếu được lấy bằng phương pháp sinh thiết (96,4%) và tại vị trí u phổi nguyên phát (87,8%). Nghiên cứu được báo cáo bởi Hsiang-Ling Ho và cs (2019) cho thấy 8,8% (13/148) tổng số bệnh nhân ung thư biểu mô tuyến vảy và ung thư biểu mô vảy có đột biến gen EGFR, trong đó 53,8% đột biến L858R trên exon 21, 30,8% là đột biến xoá đoạn trên exon 19 và 15,4% là đột biến kép L858R trên exon 21 và T790M trên exon 20 [9]. Một nghiên cứu khác của Amit Joshi và cs (2017) báo cáo rằng tỷ lệ đột biến gen EGFR ở bệnh nhân UTBMV là 4,5% (29/639).…”
Section: Bàn Luậnunclassified